3,4-Bis[(4-methoxybenzoyl)methylsulfanyl]thiophene - Ozbey, Süheyla; Kaynak, F Betül; Ertas, Erdal; Ozturk, Turan (International Union of Crystallography (IUCr), 2005)
A new type of thiophene derivative having alpha-thioketone groups at the 3- and 4-positions, viz. the title compound, C22H20O4S3, has been prepared and studied by NMR spectroscopy and single-crystal X-ray diffraction techniques. The molecule is nearly planar, the dihedral angles between the essentially planar thiophene and benzene rings being 9.4 (1) and 10.6 (1) degrees. One of the thioketone O atoms is involved in an intermolecular C-H...O hydrogen-bonding interaction.